Nodular eruption in a 7-month-old baby girl with influenza A (H1N1). - Bonifazi, E.; Neri, I.; Di Bari, C.; Merico, G. (European Journal of Pediatric Dermatology, 2011)
A 7-month-old baby girl with continuous- remittent fever from 10 days, persistent cough, elevated aminotransferases, C-reactive protein 187.8 mg/L (v.n. 0-5) was sent from the infectious department. The chest X-ray was normal. The patient had received numerous antibiotics without any improvement. For four days the child had acrolocated nodular lesions. Physical examination showed about thirty nodular lesions of the face and limbs, especially lower (Fig. 1), 1-3 cm in diameter, of hard consistency, slightly painful, movable on the deep layers; in the plantar region two nodules suppurated (Fig. 2). A biopsy was programmed. The next day, the PCR on the naso-pharyngeal swab was positive for influenza A (H1N1)v and the nodules began to regress.The final diagnosis was nodular eruption in a subject with influenza due to A (H1N1)v.